Association of Pulse Prssure Index With Mortality in Patients With Hypertension: Results From NHANES 1999–2018 - Hongjin Jin; Shusheng Fang; Shuo An; Yanchun Ding (The Journal of Clinical Hypertension)
ABSTRACT Vascular compliance is an important predictor of cardiovascular disease and mortality. Pulse pressure index (PPI) is a reliable indicator for evaluating vascular compliance. However, the association between PPI, all‐cause mortality (ACM), and cardiovascular mortality (CVM) in patients with hypertension is still unclear. In this study, we aimed to investigate the association of PPI with ACM and CVM in patients with hypertension. Kaplan–Meier survival curves, Cox proportional hazards regression models, restricted cubic splines, and subgroup and interaction analyses were used to investigate the association of PPI with ACM and CVM. U‐shaped associations were observed between PPI and both ACM and CVM, and the inflection points for ACM and CVM were at PPI values of 0.327 and 0.363, respectively. Time‐dependent receiver operating characteristic curves indicated that PPI showed good predictive value for both ACM and CVM occurrence at 1, 3, 5, and 10 years, and its predictive value was higher than PP for ACM and CVM at 5 and 10 years. These results showed that PPI can be used to identify patients with hypertension who are at a high risk of mortality and can guide more aggressive anti‐hypertensive treatment strategies. Moreover, these findings demonstrate that PPI is a superior vascular compliance indicator than PP.